DIGITAL MEDIA INFORMATION LITERACY PROGRAM FOR TEACHER - Clara Novita Anggraini; Mirah Pertiwi (Charity : Jurnal Pengabdian Masyarakat, 2022)
The development of Information and Communication Technology (ICT) is very rapid. APJII 2020 data revealed that internet penetration in Indonesia reached 73.7% (196.7 million people) of the entire Indonesian population of 267 million people. This condition allows the dissemination of information so quickly and easily, whether it is positive and useful information or hoaxes. This also has an impact on the world of education. The sophistication of the internet is misunderstood as a learning method. As a result, plagiarism and googling exam answers have become a habit for students. Therefore, the community service team created an information literacy education program for the teacher community. This program aims to introduce the concept of information literacy, how to verify hoaxes, plagiarism and how to write articles for teaching materials. The methods used are webinars, FGDs, writing reflections, and guidance on writing articles for teaching materials. The results of the program evaluation showed an increase in the information literacy skills of the participants. Articles written on teaching materials for teachers are published as an ISBN book with the title "My Class Story".